â€œGEGER BHUMI ANJUK LADANGâ€ STUDI GERAKAN SOSIAL KYAI PENOPPO DAN SOSRO KOESOEMO - kusairi, latif; Siswanto, Depy Tri Budi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The social movement was born as a result of the repressive actions of the holders of suzereinitas to the people. Regulations that bind the community, especially in the social and economic fields, make an integrated community to struggle. This is part of the class struggle for justice. Afdeeling Berbek, which was de jure as a colonial territory, experienced a storm due to social movements. This research uses the Historical method. Hisyorical research consist of four research syntaxes, namely heuristics, criticism, interpretation and historiography. The historical review of this research is to explain the relationship between the existence of two major figures involved in social movements, namely Kyai Penoppo and Sosro Koesoemo. The results of study explain about Kyai Penoppo who is a figure who has historically been respected as a religious leader and leader in the fight against colonial subversive acts in Afdeeling Berbek. This resistance occurred when the Afdeeling Berbek suzereinitas held by Sosro Koesoemo I. The overall policy issued by Sosro Koesoemo I was influenced by the central policy of Karesidentie Kediri or directly from Batavia. The influence of Kyai Penoppo in Nganjuk is still thick today, as is Sosro Koesoemo I (Kanjeng Jimat).Â Keywords: Social Movement; Kyai Penoppo; Sosro Koesoemo